Student Athlete Achievement Development at the Youth and Sports Department of Central Java Province - Barda Briliand Dian Addina; Setya Rahayu (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
The development of student athletes is a strategic effort to improve athletic performance. However, its implementation still faces various challenges, such as fluctuating performance levels at national events, budget constraints, a lack of competitive events, limited facilities and infrastructure, and the suboptimal continuity of development following the Student Sports Education and Training Center (PPLOP) program. These conditions indicate a gap between the designed development system and the results on the ground. This study aims to analyze the role of Department of Central Java Provincial Youth and Sports in the development of student athletes through the PPLOP program. The study employs a qualitative approach using interview, observation, and documentation techniques, analyzed through triangulation. The results indicate that development has been conducted in a structured and sustainable manner through systematic training programs, objective selection, and regular monitoring. Supporting factors include budgetary support, stakeholder coordination, coach competence, and facilities. Hindering factors include budget constraints, a lack of competitions, limited facilities, and the lack of optimal sustainability in development. In conclusion, the development of student athletes in Central Java is generally good, but it requires strengthening in the areas of sustainability, facilities, and the provision of competitions to enhance the athletes’ competitiveness.